Jewish and Christian scripture as artifact and canon - Evans, Craig A.; Zacharias, H. Daniel (Library of Second Temple studies, 2009)
Introducing Jewish and Christian scripture as artifact and canon / Craig A. Evans, H. Daniel Zacharias -- Oracle collection and canon : a comparison between Judah and Greece in Persian times / Armin Lange -- Artifactual and hermeneutical use of Scripture in Jewish tradition / Marianne Schleicher -- Early Christian manuscripts as artifacts / Larry W. Hurtado -- Physical features of excerpted Torah texts / Stephen Reed -- Papyrus 967 and the text of Ezekiel : parablepsis or an original text? / John Flanagan -- A fragmentary psalter from Karanis and its context / Gregg Schwendner -- 'He that dwelleth in the help of the highest' : Septuagint Psalm 90 and the iconographic program on Byzantine armbands / Thomas J. Kraus -- Public and private : second- and third-century gospel manuscripts / Scott D. Charlesworth -- A Johannine reading of Oxyrhynchus Papyrus 840 / Pamela Shellberg -- How long and old is the codex of which P.Oxy. 1353 is a leaf? / Don Barker -- Letter carriers in the ancient Jewish epistolary material / Peter M. Head -- 'I was intending to visit you, but ...' : clauses explaining delayed visits and their importance in papyrus letters and in Paul / Peter Arzt-Grabner -- Advice to the bride : moral exhortation for young wives in two ancient letter collections / Annette Bourland Huizenga -- Scribal tendencies in the Apocalypse : starting the conversation / Juan Hernández Jr. -- 'A thousand books will be saved' : Manichaean writings and religious propaganda in the Roman empire / Eduard Iricinschi -- The Danish hymnbook : artifact and text / Kirsten Nielsen -- Toward a sociology of Bible promise box use / David J. Chalcraft -- The Bible as icon : myths of the divine origins of Scripture / Dorina Miller Parmenter